Cancer outcomes among Parkinson's disease patients with leucine rich repeat kinase 2 mutations, idiopathic Parkinson's disease patients, and nonaffected controls. Issue 9 (26th July 2019) - Agalliu, Ilir; Ortega, Roberto A.; Luciano, Marta San; Mirelman, Anat; Pont‐Sunyer, Claustre; Brockmann, Kathrin; Vilas, Dolores; Tolosa, Eduardo; Berg, Daniela; Warø, Bjørg; Glickman, Amanda; Raymond, Deborah; et al.
ABSTRACT: Background: Increased cancer risk has been reported in Parkinson's disease (PD) patients carrying the leucine rich repeat kinase 2 ( LRRK2 ) G2019S mutation ( LRRK2‐ PD) in comparison with idiopathic PD (IPD). It is unclear whether the elevated risk would be maintained when compared with unaffected controls. Methods: Cancer outcomes were compared among 257 LRRK2‐ PD patients, 712 IPD patients, and 218 controls recruited from 7 LRRK2 consortium centers using mixed‐effects logistic regression. Data were then pooled with a previous study to examine cancer risk between 401 LRRK2‐ PD and 1946 IPD patients. Results: Although cancer prevalence was similar among LRRK2 ‐PD patients (32.3%), IPD patients (27.5%), and controls (27.5%; P = 0.33), LRRK2‐ PD had increased risks of leukemia (odds ratio [OR] = 4.55; 95% confidence interval [CI], 1.46–10.61) and skin cancer (OR = 1.61; 95% CI, 1.09–2.37). In the pooled analysis, LRRK2‐ PD patients had also elevated risks of leukemia (OR = 9.84; 95% CI, 2.15–44.94) and colon cancer (OR = 2.34; 95% CI, 1.15–4.74) when compared with IPD patients. Conclusions: The increased risks of leukemia as well as skin and colon cancers among LRRK2‐ PD patients suggest that LRRK2 mutations heighten risks of certain cancers. © 2019 International Parkinson and Movement Disorder Society